HUBUNGAN PENGETAHUAN DAN PERILAKU MENJAGA KESEHATAN GIGI DAN MULUT SELAMA PANDEMI COVID 19 PADA WARGA DESA GUGUK DI KABUPATEN MERANGIN, JAMBI - Naning Nur Handayatun; Ryna Astika; Linda Marlia (Jurnal Bahana Kesehatan Masyarakat (Bahana of Journal Public Health), 2022)
Background: The Covid-19 pandemic that has hit the world, including Indonesia, requires changes in people's behavior to prevent its spread. The aim of the study was to determine the relationship between knowledge and behavior in maintaining oral health during the Covid-19 pandemic in residents of Guguk Village, Renah Pembarap District, Merangin Regency, Jambi Province. Method: The type of research was cross-sectional. The research population was residents of Guguk Village, Renah Pembarap District, Merangin Regency, Jambi Province, aged 20-24 years, as many as 273 people with a sample of 73 people. Data collection used a questionnaire with a Google form link which was distributed via WhatsApp. Data analysis with chi-square statistical test. Results: Knowledge and behavior of maintaining oral and dental health during the Covid-19 pandemic in adults in Guguk Village, Merangin Regency were mostly in good criteria and there was a significant relationship between knowledge and behavior in maintaining dental health during the Covid pandemic in adults in Guguk Village, Regency Merangin with p-value = 0.001. Conclusion: There is a significant relationship between knowledge and behavior in maintaining oral health during the Covid-19 pandemic.